PENGHITUNGAN VALUE AT RISK PORTOFOLIO OPTIMUM SAHAM PERUSAHAAN BERBASIS SYARIAH DENGAN PENDEKATAN EWMA - Buchdadi, Agung D. (Jurnal Akuntansi dan Keuangan Indonesia, 2008)
The objective of this research is to examine maximum losses when investor invests on syariah based stock. Markowitz model is used for constructing the optimal portfolio. Value at Risk Model is also used for calculating the expected losses. The research indicates that volatility seems to cluster in a predictable fashion. Therefore the research forecasts variances used exponentially weighted moving average (EWMA) model. This research also aims to evaluate whether the EWMA model can predict variances reasonably well. The data used in this research are syariah based stock which had been included in Jakarta Islamic Index (JII) during the year 2005—2006. This research provides that VAR models using an EWMA forecast are good enough for predicting risk. The number of exception of 508 daily datas are only less than 5% or valid at confident level 95%. As benchmark we also use historical method and monte carlo simulation to compare performance of EWMA forecast.